(untitled) (CIPEEX, 2025)
GPE – Gestor de Presenças Escolar This document aims to evaluate the development and functionalities of the GPE (Gestor de Presenças Escolar) application, a future initiative developed by Márcio Fellipe and Yan Marra in collaboration with CEPI - Barão do Rio Branco de Palmeiras de Goiás. The GPE is designed to streamline attendance management, enhancing the professional efficiency of educators through a digital attendance list. Additionally, the application incorporates an innovative feature that automatically sends notifications to students’ guardians in the event of absences, ensuring effective communication. The methodology employed includes an analysis of the proposed functionalities and an assessment of the anticipated impact on educator productivity. Expected results suggest a significant improvement in attendance tracking efficiency and communication with guardians. The conclusion indicates that the GPE has the potential to positively transform attendance management and foster greater integration between schools and families.